Low self-control, peer delinquency and aggression among adolescents in Malaysia - Pung, Pit Wam; Yaacob, Siti Nor; Baharudin, Rozumah; Osman, Syuhaily (Canadian Center of Science and Education, 2015)
The purpose of this study was to examine the relationships between low self-control, peer delinquency and aggression among adolescents. This cross-sectional study was conducted in Selangor, Malaysia among 413 adolescents. The participants were selected from 12 secondary schools by using Multistage Cluster Sampling Technique. Self-Control Scale (Grasmick, Tittle, Bursik, & Arneklev, 1993), The Peer Delinquency Scale (Loeber, Farrington, Stouthamer-Loeber, & Van Kammen, 1998) and Aggression Questionnaire (Buss & Perry, 1992) were used to examine the relationships between adolescents’ low self-control, peer delinquency, and aggression. Results showed that there were significant positive relationships between low self-control, peer delinquency and aggression among adolescents. The result also indicated that low self-control has an indirect effect on aggression through peer delinquency. Peer delinquency served as a partial mediator. Low self-control and peer delinquency are important factors in the development of aggression among adolescents.